동결보호제의 종류에 따른 냉동보관자가골의 골형성능에 대한 연구 - 박현욱(Hyun-Wook Park); 이백수(Baek-Soo Lee) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2005)
Purpose: Several cryoprotectants are in use to help the survival of cells during cryopreservation of bone in maxillofacial region. Among them, Me2SO(dimethyl sulfoxide), EG(ethylene glycol), sucrose were used for experimentally created defects with accompanying cryopreserved bone graft in the rabbit model. The aim of this study is to analyze the effect of above mentioned agents on bone formation using histologic and histomorphometrical methods, thus to provide experimental support for clinical application of these agents. Materials and methods: Nine rabbits were used as experimental animals. Surgical defects were created on the distal femoral heads and mesial tibial heads of each animal using trephine drill(5mm diameter and 5mm length). The harvested bones were cryopreserved in -80oC refrigerator for one week. The defects were filled with cryopreserved bone with cryoprotectants as experimental groups and cryopreserved bone without cryoprotectant as control. Then, the animals were sacrificed at 1, 2, and 3 weeks after surgery. With Goldner's modified Masson trichrome staining and semiautomatic image analysis system, we observed the change of the cells and bone formation. Results: After bone graft, bone formation and active remodeling process were examined in all experimental groups and the control. But the intensity of such activities of the control were somewhat weaker than that of the experiments. Especially Me2SO+sucrose group was the best in bone formation and bone remodeling. Me2SO group was more than that of EG group in bone fomation. Sucrose seems to be helpful in survival of the bone cell. Histologic findings showed superior bony quantity and quality in experimental groups than that in control. Conclusions: The data from this study provides the basis for future studies for evaluating the effect of cryoprotectants in the cryopreservation of bone and clinical study for predictable use of these agents. KCI Citation Count: 1